Chiriatti, Mattia C. y Trillo San José, Carmen (eds.) (2024), In and Out of the City. Female Environments, Relations and Dynamics of Space (400-1500). Paderborn: Brill/Schöningh. 249 pp. ISBN: 978-3-506-79147-4 - Miriam Urbano-Ruiz (Revista de Literatura Medieval, 2025)
Reseña a Chiriatti, Mattia C. y Trillo San José, Carmen (eds.) (2024), In and Out of the City. Female Environments, Relations and Dynamics of Space (400-1500). Paderborn: Brill/Schöningh. 249 pp. ISBN: 978-3-506-79147-4